SEPARATION OF CHROM (VI) FROM ELECTROPLATING WASTE USING POLYMER INCLUSION MEMBRANE (PIM) METHOD - Djunaidi, Muhammad Cholid; Khabibi, Khabibi; Nurfitriana, Rizka (ALCHEMY Jurnal Penelitian Kimia, 2017)
Research of chromium (VI) separation has been done using polymer inclusion membrane (PIM) method. This study aims to generate PIM, separate the metal ion chromium (VI) using PIM and determine the effect of the concentration of the feed phase, the thickness of the membrane and the amount of usage of the membrane for ion chromium (VI) diffusion.Polymer inclusion membrane (PIM) was made by mixing Aliquat 336-TBP as carrier compounds, PVC as the base polymer, DBE as a plasticizer and THF as a solvent. PIM membrane was placed between the source of analyte as a feed phase and result of the separation as a receiver phase. Feed phase was electroplating waste metal containing chromium (VI) at pH 4, while the receiver phase was a 2 N NaCl solution with a pH 6.7. The change of variables in this study were the concentration of the feed phase at various dilution i.e., 100x, 50x and 10x, the thickness of the membrane i.e., 25 μm, 20 μm and 10 μm, and the time of membrane using i.e., 1, 2 and 3 times. The concentration of chromium (VI) diffused after separation process was analyzed by atomic absorption spectroscopy (AAS). The stability of membrane was observed by analyzing the presence of membrane’s component in the feed phase and in the receiver phase. The analysis was conducted by UV-Vis spectrophotometry. Meanwhile, scanning electron microscopy (SEM) analysis was used to determine the morphology of membrane surface.The results showed that the chromium ion concentration diffused from the feed phase was 99.24%, meanwhile the 85.88% of it diffused to the receiving phase. The highest Cr(VI) ions diffusion was occured at the first use of PIM membrane with a thickness of 10 μm and the concentration of the feed phase was 10.55 ppm (resulted from 100 times dilution). Therefore, it can be concluded that the diffusion of chromium (VI) ion was influenced by the concentration of feed phase, the thickness of membrane and the number of membrane application.